INTERVENSI PENURUNAN TINGKAT DEPRESI MELALUI EMPATHIC LOVE THERAPY - Eka Widiasari (UIN Sunan Kalijaga Yogyakarta, 2020)
Depression is the one global significant problem in the world. The prevalence of depression in Indonesia is higher than the prevalence in other countries. The risk of first developing depression increase in late adolescence and early adulthood, eventualy peaking in the middle age range (age 45-55). Empathic love therapy emphasizes on how individuals accept and love all aspects of him/herself. This research aimed to test the effectivity of empathic love in decreasing depression. This therapy was applied to 3 clients, who pass the inclusive criteria for selected participant, in 8 sessions of individual setting therapy. Clients was selected using Beck Depression Inventory-II (BDI-II). BDI-II was given before and after therapy, and one in the follow up session after therapy. BDI-II showed significant decrease in 3 clients depression from mild to normal in the end of therapy. Narrative analysis of conversation transcript showed decreases level of depression. The conclusion is empathic love therapy can decreas level of depression. Further research is needed to be held to find out effective contribution of therapy techniques to its succes and therapy’s reliability.